FORMULATION AND PHYSICAL PROPERTIES OF CANDLENUT OIL GEL POMADE (Aleurites Mollocana Wild) - Wilda Amananti; Aldi Budi Riyanta (Universitas Muhammadiyah Magelang, 2020)
The use of pomade for a long time will cause hair damage. Pomade with preferred ingredients, because it is very good for beauty and hair health. Liquid oil is one of the basic ingredients used in making pomade. Candlenut oil can be used as liquid oil for the pomade base. This article examines the formulation and physical properties of pomade from candlenut oil. There are four formulas that have been made with different F0 candlenut oils without candlenut oil, F1 with 10% candlenut oil, F2 with 20% candlenut oil, F3 with 30% candlenut oil. The difference in concentration is indicated to affect the physical differences of the candlenut oil pomade. Physical properties of Candlenut Oil Pomade gel include organoleptic, homogeneity, scattering test, sticky test. The results showed that all formulas showed homogeneous gel preparations. Formula 3, with the highest concentration of candlenut oil concentration of 30%, shows a greater dispersion than a formula with other substances reaching 6.5 cm and meets SNI standards, which will increase the adhesion, which does not meet the standard.